Podzols of Ilha Comprida (SE, Brazil): organic matter chemistry and decay features - Lopes, Josiane Millani (2016)
The most frequent soils in the São Paulo State Coastal Plain are Podzols, characterized by strong to moderate hydromorphic to well-drained podzolization with very well developed podzol-B horizons (Bh or Bhm). Podzolization processes include the effects of hydrology and rooting on profile morphology and the subsequent effects of improved drainage. A Podzol chrono-hydrosequence was described in detail on a cliff at the south coast of Ilha Comprida, a Holocene barrier island, and allowed a subdivision into four distinct groups: poorly-drained profiles, profiles with well-drained B horizons, strongly rooted profiles and superposed profiles. The morphological description and some observations about the exposure cliff were essential for grouping and differentiating the podzol profiles. Some well-drained podzols have OM-depleted mottles that are related to selective decomposition of organic matter (OM) by microorganisms. Such mottles are frequently associated to root channels. Seventeen profiles were studied, thirteen had depletion mottles scattered along the profile. Most of these mottles are whitish and are located preferentially in the horizons of transition between the E and B horizons, particularly in conditions of good drainage. Such mottles have certain morphological differences and may be grouped according to similarities in their morphology and their position in the profile. Distinct groups are: (a) concentric OM-depleted mottles; (b) circular/tubular OM-depleted mottles (burrows); (c) dotted OM-depleted mottles; (d) ghost OM-depleted mottles; (e) irregular OM-depleted mottles and (f) Fe-depleted mottles. The chemical composition of soil organic matter was studied in detail using pyrolysis in combination with gas chromatography/mass spectrometry (Py-GC/MS). Samples of all horizons of the distinct profiles studied were taken, as well as from the center of the mottle (M) and from the direct surroundings (S). The processes involved in the genesis of Podzols in the sandy coastal plain are directly related to drainage, the contribution of dissolved organic matter (DOM), the contribution of organic matter derived from roots, the chemical composition of organic matter and its decomposition by microorganisms, causing a large variation in adjacent Podzols. The well-drained Podzols differ in characteristics from the poorly drained ones in composition and deposition of OM, as well as its decomposition, which is directly related to the activity of groups of microorganisms. They also differ in the relative contribution of OM-derived from roots and DOM. There is a wide variation in the characteristics of decomposition by microorganisms between the profiles of Podzols permanently exposed to air and marine spray (the cliffs) on Ilha Comprida and those inland (pits). There are therefore two main processes that change the morphology of Podzols (OM and composition): (a) change in drainage and rooting, and (b) exposure to air.